Diagnostic challenges in the work up of hypereosinophilia: pitfalls in bone marrow core biopsy interpretation - Schwaab, Juliana; Jawhar, Mohamad; Naumann, Nicole; Fabarius, Alice; Hofmann, Wolf-Karsten; Reiter, Andreas; Metzgeroth, Georgia (Annals of hematology, 2016)
The FIP1L1-PDGFRA (FP) fusion gene is identified in a substantial proportion of patients with eosinophilia-associated myeloproliferative neoplasms (MPN-eo) who subsequently achieve rapid and durable remissions on imatinib. In the initial diagnostic work-up of hypereosinophilia (HE), histologic and immunohistochemical evaluation of a bone marrow (BM) core biopsy is considered essential for the differentiation between reactive hypereosinophilia (HER), MPN-eo and hypereosinophilic syndrome (HES). We therefore retrospectively analysed the initial reports of BM core biopsies from 116 patients who were subsequently identified as FP positive (FP+, n = 56) or FP negative/corticosteroid-responsive HER or HES (n = 60). Compared to HER or HES, detection of FP was more frequently associated with increased numbers of blasts (11/56 vs. 2/60, p = 0.007) and mast cells (23/33 vs. 7/23, p = 0.006; with expression of CD25 [11/18 vs. 2/13, p = 0.025]), and/or fibrosis (25/35 vs. 1/23, p < 0.0001). In FP+ patients, HE was correctly associated with an underlying clonal haematologic disorder in only 36/56 (64 %) of cases, but final BM diagnoses included a variety of diagnoses such as MPN-eo (n = 15), acute myeloid leukaemia (n = 8), systemic mastocytosis (n = 6), chronic myeloid leukaemia (n = 5) or unclassified MPN (n = 2). We conclude that the final evaluation of BM core biopsies in the diagnostic work-up of HE should include comprehensive morphologic (stains for myeloid blast cells, mast cells and fibres) and genetic analyses before a final diagnosis is established.